ANALYSIS OF THE IMPACT OF USING HRIS TECHNOLOGY IN IMPROVING THE EFFICIENCY OF HUMAN RESOURCE MANAGEMENT - Abu Siri (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the impact of the use of HRIS (Human Resource Information System) technology in improving the efficiency of human resource management in companies. Along with the rapid development of information technology, HRIS has become one of the crucial tools in managing data and human resource administration processes. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to HR managers and employees in several companies that have implemented HRIS. The results of the study indicate that the use of HRIS can significantly improve efficiency in managing employee data, recruitment processes, payroll, and performance reporting. The use of HRIS also minimizes human error, speeds up workflows, and provides more transparent access to information for managers and employees. This study is expected to provide insight for companies in considering the adoption of HRIS technology as a solution to improve overall human resource management performance.